Original paperEffects of allergic diseases, concomitant with allergic rhinitis, on the clinical efficacy and costs of allergen-specific immunotherapy in Poland - Jahnz-Rozyk, Karina; Targowski, Tomasz; Owczarek, Witold; Przekora, Piotr; Kucharczyk, Aleksandra; Wesołowski, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Aim : Evaluation the clinical efficacy of allergen-specific immunotherapy (SIT), while assessing its effects on direct cost reduction in the symptomatic therapy of allergic disease, depending on the concomitance of allergic bronchial asthma (BA), oral allergy syndrome (OAS) and/or atopic dermatitis (AD) in patients with allergic rhinitis. Material and methods : The study comprised 76 subjects above 16 with allergic rhinitis, qualified for SIT (Allergopharma-Nexter, Reinbeck, Germany). Results : Among 30 female and 46 male subjects in the study group, BA was the allergic disease most often concomitant with allergic rhinitis. The OAS syndrome was identified in 29 and AD in 15 patients. The pre-SIT index of disease symptoms in the study group was 23.1 (21.7-24.5) points, while the after-SIT index decreased considerably, down to 5.3 (4.3-6.4) points (p = 0.000001). During the pre-SIT year, the mean annual costs of symptomatic treatment, assessed from the social perspective, amounted to PLN 967.4 (737.5-1197.4) (EUR 1 = PLN 4.0; year 2008). Following the 3-year SIT therapy, the mean annual cost of symptomatic therapy fell to PLN 306.8 (176.4-437.1) (p = 0.000001). Significant positive correlations were observed in patients with coexisting allergic rhinitis and allergic BA and the rate of saving in symptomatic therapy after SIT. Conclusions : Clinical efficacy of SIT is higher in patients with allergic rhinitis and concomitant BA or the OAS than in cases of allergic rhinitis concomitant with AD. Key words: allergy, allergic rhinitis, atopic dermatitis, bronchial asthma, the oral allergy syndrome, specific immunotherapy.